Analysis of the Effectiveness of Antihypertensive Drugs on Blood Pressure Reduction in Patients Receiving Calcium Channel Blocker and Angiotensin Receptor Blocker Therapy - Fauziah; Reina Meilani; Zahra Amalia Ristiana; Khamdiyah Indah Kurniasih; Amelia Sari; Nurmalia Zakaria (LPPM Universitas Harapan Bangsa, 2026)
This study aimed to analyze the effectiveness of antihypertensive drugs from the Calcium Channel Blocker (CCB) and Angiotensin Receptor Blocker (ARB) classes in reducing blood pressure among hypertensive patients. The study employed a retrospective observational design using medical record data collected from November 2024 to February 2025 and was conducted in four primary healthcare centers in Banyumas Regency. A total of 70 patients enrolled in the PROLANIS program were selected using purposive sampling. Data were analyzed based on changes in blood pressure and statistically tested using the One-Way ANOVA test. The results showed that the ARB + CCB combination therapy was the most frequently used regimen (50%) and achieved the lowest mean blood pressure value (129.94/77.25 mmHg) among the therapy groups. Statistical analysis indicated a significant difference in systolic and diastolic blood pressure between patients receiving monotherapy and combination therapy (p < 0.05). These findings suggest that the ARB + CCB combination therapy was associated with greater blood pressure reduction compared to monotherapy among hypertensive patients in primary healthcare settings.